Implementation of Educational Philanthropy Management through Eid al-Adha Alms Cow Program in State Elementary School 13 Pidie Jaya - Muhibuddin Muhibuddin; Khairunnisak Khairunnisak (Gestion Educativa, 2026)
The unequal distribution of Eid al-Adha sacrificial meat in madrasahs can negatively affect students’ social cohesion and psychological well-being. At MIN 13 Pidie Jaya, Aceh, this issue occurred for two consecutive years because the limited number of sacrificial animals provided through the ASN Berqurban Program could only reach a small portion of the 723 students, leading to social jealousy within the school community. To address this problem, the madrasah introduced the *Sapi Sedekah* Program, a community-based philanthropic initiative funded through voluntary student donations collected every Friday. This study aims to analyze the management of educational philanthropy through the *Sapi Sedekah* Program, identify implementation challenges and solutions, and examine its impact on character education and social cohesion. Using a qualitative single-case study design, data were collected through in-depth interviews with 10 informants, participant observation, and documentation analysis. The findings show that the program is managed effectively through POAC management functions supported by transformational leadership. Weekly donations of Rp500–Rp2,000 per student successfully generated sufficient funds to purchase one cow annually, with fund growth reaching 71.8% over three years. The equitable distribution of sacrificial meat eliminated social jealousy and strengthened social harmony. Furthermore, the program fostered moral knowing, moral feeling, and moral action among students and received strong community support. The study proposes a Community-Based Institutional Philanthropy model that can be adapted by other educational institutions..